2023
DOI: 10.1029/2022jb026140
|View full text |Cite
|
Sign up to set email alerts
|

Conduit Processes at the Haukadalur Geyser‐Hosting Hydrothermal Field (Iceland) Revealed by In Situ Temperature and High‐Speed Camera Measurements

Marine Collignon,
Laura Pioli,
Daniele Trippanera
et al.

Abstract: Geysers fascinate scientists and visitors for several centuries. However, many driving mechanisms such as heat transfer in the conduit and in the subsurface remain poorly understood. We document for the first time transient temperature variations inside the active Strokkur's and nearby quasi‐dormant Great Geysir's conduits, Iceland. While recording temperature inside the conduit, we visually monitored Strokkur's activity at the vent with a high‐speed camera, providing a high temporal resolution of the eruption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 52 publications
0
0
0
Order By: Relevance
“…In such cases, the energy released during the eruption is thus efficiently channeled into a large bulge and a large jet, while not generating much seismic ground motion. In contrast, larger jets are followed by a longer waiting time for the next one, and Collignon et al [2023] confirmed that more energy is lost during large eruptions, which must be supplied by the heat source at depth at a possibly constant rate.…”
Section: Discussionmentioning
confidence: 72%
See 4 more Smart Citations
“…In such cases, the energy released during the eruption is thus efficiently channeled into a large bulge and a large jet, while not generating much seismic ground motion. In contrast, larger jets are followed by a longer waiting time for the next one, and Collignon et al [2023] confirmed that more energy is lost during large eruptions, which must be supplied by the heat source at depth at a possibly constant rate.…”
Section: Discussionmentioning
confidence: 72%
“…number 52 in Figure 5). This indicates that some water jets are actually composed of multiple pulses, possibly caused by multiple or more complexly shaped bubbles (see work by Collignon et al [2023] for more detail on pulses).…”
Section: Stacked Jet and Drift Heights And Velocitiesmentioning
confidence: 99%
See 3 more Smart Citations